Linguistic Anthropological Analysis of Toponymy of the Names of Tukung Island and Babi Island in Balikpapan, East Kalimantan - Handayani, Wiwik Retno (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study examines the toponymy of Tukung Island and Babi Island in Balikpapan waters, East Kalimantan, through a linguistic anthropology approach. The research objective is to reveal the relationship between language, culture, and environment reflected in naming the two islands. The method used is descriptive qualitative analysis with an ethnographic approach. Data were obtained through a literature study of folklore manuscripts and secondary sources. The results show that Tukung Island comes from the word “tokong” in Malay, which means rowing pole. It is related to the legend of Panglima Sendong or refers to a small coral island according to its physical characteristics. The name Pulau Babi is associated with the presence of wild pig habitat, the shape of the island resembling a pig, or the legend of transforming humans into pigs. The analysis reveals that naming the two islands reflects the local wisdom of Balikpapan coastal communities in observing the environment and perpetuating collective experiences through language. The study also found a shift in the meaning and perception of the people towards the two island names, along with socio-cultural changes.